If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5y + 6) = 82 Reorder the terms: 2(6 + 5y) = 82 (6 * 2 + 5y * 2) = 82 (12 + 10y) = 82 Solving 12 + 10y = 82 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 10y = 82 + -12 Combine like terms: 12 + -12 = 0 0 + 10y = 82 + -12 10y = 82 + -12 Combine like terms: 82 + -12 = 70 10y = 70 Divide each side by '10'. y = 7 Simplifying y = 7
| log[7](4)-log[7](3x)= | | 0=4b^2-76b+16 | | 4x+6=5-3x | | 0=4b^2-200b+16 | | x^2+5mx+16=0 | | 0=4b^2-96b+16 | | x+7/6-x/3=-2 | | 0=12t^2-42t+30 | | 3x-2+2y+1+x-w+1+3-4w=22 | | 4t+7=9t-13 | | 25x^2-160x+220=0 | | 0=b^2-24b+4 | | 2/x+1/x-1=2 | | 0=b^2-24h+4 | | b(2x+b)=0 | | 60*5=678 | | 25x^2-16x+220=0 | | 5t^2+30t+4=0 | | 60/5=12 | | Custo(x)=4x+4000 | | (x)=4x+4000 | | 01*x+04=2 | | 5x^2-16x+44=0 | | y=-x+6-2 | | 2j+y=60 | | 11x+9=11x+18 | | (1+x)=0.4535 | | Mn-m^2n+mn^2=0 | | (3a-7b)-(4a-b)= | | 4*2+11X-4=0 | | -8(r+-2)=40 | | =-25x^2+40x-16 |